2012 18th IEEE International Conference on Networks (ICON) 2012
DOI: 10.1109/icon.2012.6506551
|View full text |Cite
|
Sign up to set email alerts
|

On the connectivity of wireless networks with multiple directional antennas

Abstract: Abstract-The network connectivity is one of important measures of the performance of wireless networks. However, most of current studies on the network connectivity only consider either an SOMN network, where each node is mounted with a single omni-directional antenna, or an SDA network, where each node is mounted with a single directional antenna. Using multiple directional antennas instead of a single directional antenna can potentially improve the network performance. In this paper, we investigate the conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The reason lies the fact that using directional antennas in wireless networks can establish some long links to connect the nodes that are far away and even out of the transmission range of an isotropic antenna. This result further confirms the results [8]- [10].…”
Section: A Connectivity Comparison With Uca Antenna Isotropic Antensupporting
confidence: 82%
See 1 more Smart Citation
“…The reason lies the fact that using directional antennas in wireless networks can establish some long links to connect the nodes that are far away and even out of the transmission range of an isotropic antenna. This result further confirms the results [8]- [10].…”
Section: A Connectivity Comparison With Uca Antenna Isotropic Antensupporting
confidence: 82%
“…Recently, many studies [4]- [10] show that using directional antennas instead of omni-directional antennas in wireless ad hoc networks can significantly improve the network performance (particularly for the network connectivity). The performance improvement mainly owes to the reduction in the interference from undesired directions and the extension in the transmission range because directional antennas concentrate radio signals on the desired directions.…”
Section: Introductionmentioning
confidence: 99%
“…This was analytically pushed down to 2 in [20] where it was also shown that this number is independent of the small-scale fading model used. Finally, the possibility of using multi-directional antennas was proposed and studied in [21], and although unmotivated, was reported to enhance connectivity at low path loss.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption applies for all the above three scenarios. In addition, we also assume that the orientation of either a simplistic directional antenna in Scenario (ii) or a realistic directional antenna in Scenario (iii) is randomly chosen from a uniform distribution on the interval [0, 2π] (similar to [15], [17]). We then analyze the eavesdropping activities under the above three scenarios.…”
Section: B Eavesdropping Model 1) Channel Modelmentioning
confidence: 99%